Análisis de la táctica ofensiva en situación de asimetría (6 contra 5) en la liga ASOBAL de balonmano - Vallejo Ruiz, M. (2016)
The aim of this project is to study situations produced by numerical asymmetry 6 to 5 in handball. For that purpose, we are going to analyze the fifteen matches between the best six teams in the league ASOBAL 2014-2015 season. In this sample we have obtained 142 shares from which, once they have been edited, different variables have been analyzed. From the results, it was highlighted that the most commonly used geometric structure offensive (GSO) is 3:3 with a pivot, and the geometric structure defensive (GSD) given by most teams is 5: 0. The most used number of passes (NP) is between 1 and 3 with a length (DA) between 3 and 6 seconds. The most often used basic tactical offensive ways (BTO) are the intersection (I), blocking (BL) and the exchange (E). The result sequence (RS) was further success in the launch (SL). Most often the starter player (SP) of the action was the central one (B), with completions by the launch interval (LI) of the left one (F), being this the one that most shots made (LP) at a distance of release (DR) of 6 meters. Often with a location of the pivots (LP) in E2 and E3. Regarding efficiency, the most effective offensive geometric structure (GSO) is 3: 3 (1P) and the most vulnerable geometric structure defensive (GSD) was 4: 1. Best results with intersection (I) and exchange (E) initiating the right side player (C), with pivots located on E1 or E2, throwing the right side player (C)